2020
DOI: 10.1007/s40279-020-01337-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plyometric Jump Training on Jump and Sprint Performance in Young Male Soccer Players: A Systematic Review and Meta-analysis

Abstract: Effects of plyometric jump training on jump and sprint performance in young male soccer players: a systematic review and meta-analysis. Sports Medicine. In press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 125 publications
9
68
1
1
Order By: Relevance
“…One specific type of power training that is easy to administer and therefore popular is plyometric jump training (PJT) (Ramirez-Campillo and Castillo, 2020;Ramirez-Campillo et al, 2021a;Sole and Ramírez-Campillo, 2021). PJT consists of exercises which take advantage of the stretch-shortening cycle (SSC) of the muscle (Komi and Gollhofer, 1999;Taube et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One specific type of power training that is easy to administer and therefore popular is plyometric jump training (PJT) (Ramirez-Campillo and Castillo, 2020;Ramirez-Campillo et al, 2021a;Sole and Ramírez-Campillo, 2021). PJT consists of exercises which take advantage of the stretch-shortening cycle (SSC) of the muscle (Komi and Gollhofer, 1999;Taube et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The specialized literature highlights very few studies on football-tennis, and the many identified studies focus mainly on the management of the game and the technical training of football-tennis players [53,54]. We consider the results of our study to complete the conclusions of recent studies conducted on 12 football players [55], respectively, and on 40 football players [56], over a period of 8 months of endurance training combined with plyometric exercises/strength training program, which showed significant improvements in muscle strength and jump ability [57,58]. The level of explosive force can contribute to improving performance and sporting success.…”
Section: Discussionmentioning
confidence: 74%
“… 31 , 32 Sprinting, which is the most common action when scoring goals for young soccer players, 13 is one of the important determinants of high-level youth soccer performance. 33 , 34 Within a soccer match, such actions repeatedly generate explosive oscillations and impacts, using the SSC, requiring fast force generation and high-power output. In short, almost every explosive movement during a soccer match involves SSC, 35 during which the previously stimulated muscle is first stretched (eccentric action), and then shortened (concentric action).…”
Section: Introductionmentioning
confidence: 99%